Altered Motor Excitability in Patients With Diffuse Gliomas Involving Motor Eloquent Areas: The Impact of Tumor Grading. Issue 1 (5th September 2020) - Lavrador, José Pedro; Gioti, Ifigeneia; Hoppe, Szymon; Jung, Josephine; Patel, Sabina; Gullan, Richard; Ashkan, Keyoumars; Bhangoo, Ranjeev; Vergani, Francesco
Abstract: BACKGROUND: Diffuse gliomas have an increased biological aggressiveness across the World Health Organization (WHO) grading system. The implications of glioma grading on the primary motor cortex (M1)-corticospinal tract (CST) excitability is unknown. OBJECTIVE: To assess the excitability of the motor pathway with navigated transcranial magnetic stimulation (nTMS). METHODS: Retrospective cohort study of patients admitted for surgery with diffuse gliomas within motor eloquent areas. Demographic, clinical, and nTMS-related variables were collected. The Cortical Excitability Score (CES 0 to 2 according to the number of abnormal interhemispheric resting motor threshold (RMT) ratios) was calculated for patients where bilateral upper and lower limb mapping was performed. RESULTS: A total of 45 patients were included: 9 patients had a low-grade glioma and 36 patients had a high-grade glioma. The unadjusted analysis revealed an increase in the latency of the motor evoked potential of the lower limb with an increase of the WHO grade ( P = .038). The adjusted analysis confirmed this finding ( P = .013) and showed a relation between the increase in the WHO and a decreased RMT ( P = .037) of the motor evoked responses in the lower limb. When CES was calculated, an increase in the score was related with an increase in the WHO grade (unadjusted analysis— P = .0001; adjusted analysis— P = .001) and in isocitrate dehydrogenase (IDH) wild-type tumors (unadjusted analysis— P = .020). CONCLUSION: An increase in the WHO grading system and IDH wild-type tumors are associated with an abnormal excitability of the motor eloquent areas in patients with diffuse gliomas. Graphical Abstract: